Ultrathin Anatase TiO2 Nanosheets for High‐Performance Photocatalytic Hydrogen Production. Issue 16 (20th February 2017) - Li, Ming; Chen, Ying; Li, Wei; Li, Xiang; Tian, He; Wei, Xiao; Ren, Zhaohui; Han, Gaorong
Abstract : An ethanol solvothermal route has been developed to prepare ultrathin anatase TiO2 nanosheets with dominant {001} facets (≈97%), a thickness of ≈2.5 nm, and a side length of ≈200 nm. The introduction of ethanol solvent significantly enhances the content of surface chemisorbed F − on the TiO2 nanosheet, which has a higher stability and further lowers the surface energy of {001} facets, giving rise to the large percentage of active {001} facets. Adopting well‐defined morphology, such nanosheets loaded with 1 wt% Pt exhibit an H2 evolution rate as high as 17.86 mmol h −1 g −1, and the corresponding apparent quantum efficiency has been determined to be 34.2%. Abstract : Ultrathin anatase TiO2 nanosheets of ≈2.5 nm in thickness and ≈200 nm in side‐length are prepared with an ethanol solvothermal route, giving rise to ≈97% {001} facets exposed. Such nanosheets exhibit an H2 evolution rate as high as 17.86 mmol h −1 g −1, and the corresponding apparent quantum efficiency is determined to be 34.2%.